Choice proliferation, simplicity seeking, and asset allocation - Iyengar, Sheena S.; Kamenica, Emir (Journal of public economics, 2010)
In settings such as investing for retirement or choosing a drug plan, individuals typically face a large number of options. In this paper, we analyze how the size of the choice set influences which alternative is selected. We present both laboratory experiments and field data that suggest larger choice sets induce a stronger preference for simple, easy-to-understand options. The first experiment demonstrates that, in seeming violation of the weak axiom of revealed preference, subjects are more likely to select a given sure bet over non-degenerate gambles when choosing from a set of 11 options than when choosing from a subset of 3. The second experiment clarifies that large choice sets induce a preference for simpler, rather than less risky, options. Lastly, using records of more than 500,000 employees from 638 institutions, we demonstrate that the presence of more funds in an individual's 401(k) plan is associated with a greater allocation to money market and bond funds at the expense of equity funds.